Fighting the Russians in winter : three case studies. - Chew, Allen F. (Fort Leavenworth, KS: Combat Studies Institute, US Army Command and General Staff College, 1981)
This paper contains three case studies about winter warfare drawn from twentieth century experience. It provides several valuable perspectives about this well known, but sometimes little understood subject. Our attention is directed to the distinctive aspects of warfare in subarctic climes, the characteristics of this harsh environment and the climatic impact upon a broad range of military operations. These case studies also provide examples of how several armies adapted-or failed to adapt-to the demands of winter warfare. Finally, they demonstrate that even military forces indigenous to subarctic regions, with experienced soldiers, can have difficulty in conducting winter operations.